Bi-Te Thin Film Produced by Ion Beam Sputtering: Impact of Beam Voltage in the Seebeck Coefficient. (2017) - Pires, A.L.; Cruz, I.F.; Ferreira-Teixeira, S.; Resende, P.M.; Pereira, A.M.
Abstract: The preparation of high-quality, economic and scalable thin films are crucial for future applications in efficient thermoelectric devices. Ion Beam sputtering deposition appears as an elegant solution to tackle this challenge and in this context it will be used in this work. Thus herein, we assess the influence of the beam voltage in the thermoelectric properties through a thorough study of the morphological, chemical and transport properties in the produced thin films. It outcome that beam voltage drastically influences the stoichiometry leading to different crystalline structures that directly affect the thermoelectric properties of the Bi-Te deposited thin films.